Improvement structure and electrical properties of ITO thin films by annealing treatment - Srithanachai, I.; Sangwaranatee, N. (My University, 2024)
In this paper present, the improvement of ITO thin films properties by thermal annealing treatment by various temperature. The process for this investigation various temperature 100-500 ◦C under nitrogen environment, control time for 23 mins. The films crystallization improves after annealing process by XRD results show strong peak after post-annealing and resistivity of thin films shows significant reduced from 1996 to 706 O-cm. The films crystallization shows small peak after thin film growth, however treatment process induced strong peak (222) and (441). The optimization point of treatment process can improve thin films properties that can apply thin films for low energy photodiode.
Keywords: Annealing treatment; ITO; Sputtering process; Thin films